Effects of Terlipressin on Management of Hypotensive Brain-Dead Patients Who are Potential Organ Donors: A Retrospective Study - Zheng, Donghua; Liu, Genglong; Chen, Li; Xie, Wenfeng; Sun, Jiaqi; Wang, Siqi; Tai, Qiang (Frontiers in Pharmacology, 2021)
Background：Administration of terlipressin can reverse hypotension in potential organ donors with norepinephrine-resistance. The aim of this study was to determine the effects of terlipressin on the hemodynamics, liver function, and renal function of hypotensive brain-dead patients who were potential organ donors. Methods: A retrospective study was conductedby using the ICU database of one hospital. 18 patients in a total of 294 brain-dead cases were enrolled and administered terlipressin intravenously. All physiological parameters of recruited patients were obtained at baseline, 24 h and 72 h after administration, and immediately before organ procurement. Results: Terlipressin induced significant increases in mean arterial pressure (MAP) from 69.56 ± 10.68 mmHg (baseline) to 101.82 ± 19.27 mmHg (immediately before organ procurement) and systolic blood pressure (SBP) from 89.78 ± 8.53 mmHg (baseline) to 133.42 ± 26.11 mmHg (immediately before organ procurement) in all patients. The increases in MAP were accompanied by significant decreases in heart rate (HR) from 113.56 ± 28.43 bpm (baseline) to 83.89 ± 11.70 bpm (immediately before organ procurement), which resulted in the decrease of norepinephrine dose over time from 0.8 ± 0.2 μg/kg/min (baseline) to 0.09 ± 0.02 μg/kg/min (immediately before organ procurement). There were no changes in central venous pressure, liver function including aspartate aminotransferase (AST), alanine aminotransferase (ALT), and bilirubin. Renal function, assessed by serum creatinine (SCr), urine output (UOP), creatinine clearance rate (CCr), and estimated glomerular filtration rate (eGFR), improved significantly. Conclusions: Our analysis of brain-dead patients with hypotension indicates that administration of terlipressin can significantly increases MAP, SBP, UOP, CCr, and eGFR, while decreases HR and Scr. Terlipressin appears to help maintain hemodynamic stability, reduce vasoactive support, and improve renal function.